In silico and In vitro Study of The Anticancer Potential of Essential Oil from Sembung (Blumea balsamifera) Leaves against HeLa Cervical Cancer Cells - Ulia, Rahmi Vika; Raharto, Toto; Suryati; Santoni, Adlis; Herru, Yoan De Nanda (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2026)
Blumea balsamifera (L.) DC. (sembung) is a medicinal plant widely recognized for its diverse pharmacological properties, including cytotoxic and anticancer activities. However, the anticancer potential of its leaf essential oil against cervical cancer remains poorly explored. This study aimed to evaluate the anticancer activity of B. balsamifera leaf essential oil against HeLa cervical cancer cells using integrated in silico and in vitro approaches. Molecular docking analysis against the anti-apoptotic Bcl-2 protein revealed favorable binding affinities for several major constituents, including camphor (-5.745 kcal/mol), caryophyllene (-7.077 kcal/mol), 7-epi-silphiperfol-5-ene (-7.311 kcal/mol), and γ-eudesmol (-7.083 kcal/mol), indicating potential interactions with apoptosis-related targets. Furthermore, cytotoxic activity assessed by the MTT assay demonstrated an IC₅₀ value of 32.90 µg/mL against HeLa cells, indicating moderate cytotoxic potency. These findings suggest that B. balsamifera leaf essential oil possesses promising anti-cervical cancer activity and may serve as a potential natural source for the development of apoptosis-targeting anticancer agents.